Pengaruh Promosi, Citra Merek, Brand Ambassador, dan Kualitas Produk Terhadap Keputusan Pembelian Somethinc - Farah Rizqy Salsabila; Alfalisyado; Tri Septin Muji Rahayu; Alfato Yusnar Kharismasyah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This purpose of this study is understand how consumer characteristics and analyze the effect of promotion, brand image, brand ambassador, and product quality on purchasing decisions on Somethinc products. The method used in this study is quantitative method. The number of samples in this study were 114 respondents who were determined by purposive sampling technique with the criteria of active university students in Purwokerto City who had purchased Somethinc products. The data analyzed is primary data collected using a questionnaire and processed by multiple regression analysis methods using the SPSS program version 26. Instrument testing states that all indicators are valid and all variables are declared reliable. The t-test results show that the promotion and brand image variables partially have a positive and significant effect on purchasing decisions, while the brand ambassador and product quality variables do not affect purchasing decisions. The F test results show that the regression model in this study is suitable for hypothesis testing. The coefficient of determination (Adj. R2) test results show the ability of the independent variables to explain the dependent variable by 59.1%.